(untitled) (Jurnal TEKNODIK, 2017)
ABSTRAK:Penelitian ini bertujuan untuk mengetahui perbandingan tingkat pemahaman konsep matematika siswa melalui media interaktif mischief dan media konvensional pada materi relasi dan fungsi. Objek penelitian ini adalah siswa kelas VIII Madrasah Tsanawiyah Negeri 20 Jakarta Tahun Ajaran 2014/2015. Kelas VIII-1 ditetapkan sebagai kelas eksperimen dan kelas VIII-2 sebagai kelas kontrol. Proses pembelajaran di kelas eksperimen menggunakan media interaktif mischief sedangkan kelas kontrol menggunakan media konvensional. Metode penelitian yang digunakan adalah quasi eksperimen dengan hipotesis terdapat perbedaan tingkat pemahaman konsep matematika siswa melalui media interaktif mischief dan media konvensional. Hasil penelitian menunjukkan bahwa terdapat perbedaan tingkat pemahaman konsep matematika siswa melalui media interaktif mischief dan media konvensional. Hal ini terbukti dari hasil perhitungan yang menunjukkan hasil uji-t (dua pihak) sebesar 2,162 lebih besar dari ttabel yakni 1,991 (2,162 > 1,992). Selain itu, hasil perhitungan uji-t (satu pihak) menunjukkan t hitung sebesar 2,162 lebih besar dari ttabel sebesar 1,665 (2,162 > 1,665). Berdasarkan hasil analisis data dapat disimpulkan bahwa rata-rata pemahaman konsep siswa yang diajar menggunakan media interaktif mischief lebih tinggi dari pada siswa yang diajar menggunakan media konvensional. Hasil penelitian ini diharapkan mampu memberikan inspirasi bagi pihak sekolah dalam mengembangkan media pembelajaran yang berbasis Teknologi Informasi dan Komunikasi. Kata Kunci: pemahaman konsep matematika, audio visual, mischief, relasi dan fungsi. ABSTRACT:The objective of this study was to get to know the comparison between mathemtical concept understanding by students trough â€œmischiefâ€ interactive media and conventional media on the material of relations and functions. The object was the students of grade VIII at MTs Negeri 20 Jakarta in 2014/2015 Academic Year. Grade VIII-1 was stated to be the experimental class and grade VIII-2 was as the control class. The experimental class was taught by using mischief interactive media while the control class was taught by using conventional media. This study used quasi experiment with the hypothesis that there was difference in understanding level on mathematical concept by students taught by using mischief interactive media and those taught by conventional media. The result showed that there was difference in the use of mischief interactive media and conventional media in terms of the studentsâ€™ understanding level on mathematical concept at experimental class and control class. This was proven by the result of calculation showing the result of t-test (two parties) amounting to 2.162 greater than ttable which was 1.991 (2.162> 1.992). In addition, the calculation result of t-test (one-party) showed that t hitung 2.162 was greater than ttabel 1.665 (2.162> 1.665). Based on the data analysis, it can be concluded that the average of studentsâ€™ understanding on mathematical concept taught by using mischief interactive media was higher than those taught by using conventional media. This study result is expected to be inspiring schools in developing information and communication technology based learning material. Keywords: mathematical concept understanding, audio visual, mischief, relations and functions.